WATER SCARCITY AND IMPACT ON SUSTAINABLE ECONOMIC DEVELOPMENT IN THE AGRICULTURAL SECTOR AND TOOLS TO ADDRESS IT IN IRAQ (Review Article): WATER SCARCITY AND IMPACT ON SUSTAINABLE ECONOMIC DEVELOPMENT IN THE AGRICULTURAL SECTOR AND TOOLS TO ADDRESS IT IN IRAQ (Review Article) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The study aims to use some strategies such as water footprint and water trade to confront the challenges of water scarcity to promote sustainable development in the agricultural sector and its development. In recent years, Iraq has been suffering from water scarcity due to the lack of water releases in the Tigris and Euphrates rivers as a result of their reduction by upstream countries such as Turkey and Iran. Water revenues in 2022 amounted to about 25.5 billion cubic meters after reaching about 93 billion cubic meters in recent years. Which requires working on proper water management, involving all stakeholders in making the necessary decisions, drawing up appropriate agricultural policies, and making use of water footprint concepts to determine which crops can be grown that need small amounts of water and have a good economic return that does not conflict with the level of self-sufficiency as well as using Virtual water trade to enhance water and food security and achieve sustainable development in the agricultural sector. Therefore, the government is requested to develop a plan to program water uses, determine the best ways to manage the water crisis, and name a high-level committee that takes responsibility for all water-related decisions.